Language, Rights and Legal Culture - Gulyamova Gulnora Yakubovna; Nurshasha Almatova (Peerian Journals Publishing, 2023)
The requirement of the time is to further increase the influence and status of our native language in the life of the state and society, to ensure the full implementation and acceleration of the state language in our country, approaching it with a spirit of devotion to one's work, an international idea. In this regard, the full and correct use of the potential of the literary language in all areas of the socio-political life of our country (including jurisprudence) is one of the priorities of state policy. Ensuring the rule of law in society is one of the important principles of a democratic state governed by the rule of law, for which laws must be fair in nature and understandable to people, that is, the language of the created legal documents must be detailed and fluent. In this article, law and language, which are two sides of the same process, their relationship, the requirements for strict adherence to the norms of the literary language, the written legal language, the vocabulary of the legal language in the formal style of correspondence, oral and written forms, legal formulations, features, some shortcomings in connection with that, ways to overcome them
Keywords: jurisprudence; law; language; communicative and literary literacy